Materia i forma sakramentu małżeństwa - Janczewski, Zbigniew (Ius Matrimoniale, 2013)
Two of few elements which have an influence on validity of the sacraments administration are the matter and form. The most important is the fact if they were defined directly by the very Jesus Christ and they are in the deposit of revelation. Otherwise, they are defined by the Church, which specifies them by means of canonical and liturgical law, the conditions for a sacrament to be valid. The gesture of a minister of a sacrament is the matter of a given one, which is necessary for validity of an act and for receiving a sacramental grace, while the words spoken by him during the celebration of a sacrament (that is a sacramental formula), included in the liturgical books, constitute the form. But is a problem with sacrament of marriage. The matter and form of such sacrament are different in the Roman catholic and orthodox Churches. In the first of those the matter is matrimonial consent. It is an act of will by which a man and a woman by an irrevocable covenant mutually give and accept one another for the purpose of establishing a marriage. The form is formula of consent. In the orthodox Church the matter is priest’s or bishop’s blessing, and the form is formula of such blessing. This article shows history of the matter and form of those sacrament and various problems relative this questions.